Ad Hoc wireless networks : architectures and protocols - Murthy, C. Siva Ram, ....-; Manoj, B. S., ....- (Upper Saddle River, NJ : Prentice Hall/PTR, 2004)
Expert guide to the fundamental concepts, issues, and state-of-the-art developments in Ad Hoc Wireless Networking. Thorough coverage of the top level issues that effect the design and performance of Ad Hoc Wireless networks. Ad Hoc Wireless networks are efficient, budget friendly and easy to set up, making it an attractive solution in the public and private sector. Coverage includes the latest in wireless technology, such as Wi-Fi, Ultra Wide Band and Hybrid Wireless Architecture. Ad Hoc Wireless Networks can be set up anywhere and anytime as they eliminate the complexities of infrastructure setup and administration. An Ad Hoc Wireless Network is a wireless network, comprised of mobile nodes (which can also serve as routers) that use wireless transmission, having no infrastructure (central administration such as a Base Station in a Cellular Wireless Network or an Access Point in a Wireless LAN). In the last few years, there has been a big interest in Ad Hoc Wireless Networks as they have tremendous military and commercial potential. Ad Hoc Wireless Networks find applications in several areas, such as military applications (establishing communication among a group of soldiers for tactical operations as setting up of a fixed infrastructure in enemy territories or in inhospitable terrains may not be possible), collaborative and distributed computing, emergency operations, wireless mess networks, wireless sensor networks, and hybrid (integrated Cellular and Ad Hoc) wireless networks. This book first presents the fundamental topics involved with Wireless Networking such as Wireless Communications Technology, such as Utlra Wideband Technology, Wireless LANs and PANs, such as Wi-Fi Systems, Wireless WANs and MANs, Wireless Internet, Wireless Sensors Networks, and Hybrid Wireless Architecture (this is the hot topic of "cross-layer wireless networks).
Includes bibliographical references and index.
Keywords: Computer network architectures; Draadloze computernetwerken; Routers (Computer networks).; Wireless communication systems